ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR KAKAO DI INDONESIA 2015 – 2019 - Subawa, I Made Adhi; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
Cocoa is one of the plantation commodities that has an important role in economic activities in Indonesia. Cocoa is also one of Indonesia's export commodities which is quite important as a foreign exchange earner besides oil and gas. Indonesia is the world's third largest cocoa producer and exporter after Ghana and Ivory Coast. The development of cocoa exports in 2015-2019 has a fairly volatile pattern. In 2015 the total export volume of cocoa was 105.15 thousand tons and in 2017 it increased by 270.17 thousand tons. The results of this study indicate that partially the US Dollar exchange rate variable has a negative and significant effect on the volume of cocoa exports in Indonesia 2015-2019. The price variable has a positive and significant effect on the volume of cocoa exports in Indonesia 2015-2019 and the variable amount of cocoa production has no effect on the volume of cocoa exports in Indonesia 2015-2019. Simultaneously the US Dollar exchange rate, price and amount of cocoa production have a significant effect on the volume of cocoa exports in Indonesia 2015-2019 and the variable amount of cocoa production has no effect on the volume of cocoa exports in Indonesia 2015-2019. This analysis shows that the variable that has the dominant influence on the volume of cocoa exports in Indonesia from 2015-2019 is the price variable.